The Regulation of Inflammatory Pathways and Infectious Disease of the Cervix by Seminal Fluid. (11th August 2014) - Adefuye, Anthonio; Katz, Arieh Anthony; Sales, Kurt Jason
Abstract : The connection between human papillomavirus (HPV) infection and the consequent sequelae which establishes cervical neoplastic transformation and invasive cervical cancer has redefined many aspects of cervical cancer research. However there is still much that we do not know. In particular, the impact of external factors, like seminal fluid in sexually active women, on pathways that regulate cervical inflammation and tumorigenesis, have yet to be fully understood. HPV infection is regarded as the initiating noninflammatory cause of the disease; however emerging evidence points to resident HPV infections as drivers of inflammatory pathways that play important roles in tumorigenesis as well as in the susceptibility to other infections such as human immunodeficiency virus (HIV) infection. Moreover there is emerging evidence to support a role for seminal fluid, in particular, the inflammatory bioactive lipids, and prostaglandins which are present in vast quantities in seminal fluid in regulating pathways that can exacerbate inflammation of the cervix, speed up tumorigenesis, and enhance susceptibility to HIV infection. This review will highlight some of our current knowledge of the role of seminal fluid as a potent driver of inflammatory and tumorigenic pathways in the cervix and will provide some evidence to propose a role for seminal plasma prostaglandins in HIV infection and AIDS-related cancer.